Activity and Longevity of Antibody in Paper-Based Blood Typing Diagnostics - Henderson, Clare A.; McLiesh, Heather; Then, Whui L.; Garnier, Gil (Frontiers in Chemistry, 2018)
Paper-based diagnostics provide a low-cost, reliable and easy to use mode of blood typing. The shelf-life of such products, however, can be limited due to the reduced activity of reagent antibodies sorbed on the paper cellulose fibres. This study explores the effects of ageing on antibody activity for periods up to twelve months on paper and in solution under different ageing and drying conditions -- air-dried, lyophilised and kept as a liquid. Paper kept wet with undiluted antibody is shown to have the longest shelf-life and the clearest negatives. Antibody diluted with bovine serum albumin (BSA) protects against the lyophilisation process, however, beyond nine months ageing, false positives are seen. Paper with air-dried antibodies is not suitable for use after one month ageing. These results inform preparation and storage conditions for the development of long shelf-life blood grouping paper-based diagnostics.